Research progress on intranasal treatment for Parkinson's disease - Puyuan Wen; Chao Ren (Neuroprotection)
Abstract Parkinson's disease (PD) is the second most prevalent neurodegenerative disorder globally, significantly affecting the quality of life of affected individuals. Systemic drug delivery to the brain is inefficient because of first‐pass metabolism, the blood‐brain barrier (BBB), and the blood‐cerebrospinal fluid barrier. This inefficiency necessitates increased dosage as the disease progresses, leading to severe side effects that compromise the efficacy of the medication. Nose‐to‐brain (N2B) administration bypasses the BBB, allowing delivery of both small molecules and large protein substances to the central nervous system. Compared with systemic administration, this method enhances brain bioavailability, reduces enzymatic degradation, and minimizes systemic adverse reactions. However, the N2B delivery system is associated with several critical challenges, including mucociliary clearance, enzymatic degradation, and drug translocation via efflux mechanisms. This paper provides a comprehensive overview of the current research progress in intranasal treatment of PD, considering both preclinical and clinical studies, and discusses the physiological aspects and limitations of its delivery system.